Analisis Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) terhadap Kinerja Pelayanan Kesehatan di Rumah Sakit X - Anita Sriwaty Pardede (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The evaluation of information systems becomes important to ensure the effectiveness of the Hospital Information System (SIMRS) application and its positive impact in producing information that meets the standards of data quality with the HOT fit theory, which includes the core elements of the information system: human, organization, Technology and net benefits. The research was conducted using a cross-sectional design and involved 78 SIMRS users in X Hospital as the sample. Data were analysed using the partial least squares (PLS) structural equation modelling (SEM) method. The results of the study showed that user satisfaction, information quality, service quality, system quality, organizational environment, system utilization level, and organizational structure had significant relationships with SIMRS based on hypothesis testing. The significant findings included user satisfaction, net benefits, system utilization, service quality, system quality, organizational environment, and information quality. This study emphasizes the importance of routine and periodic maintenance, monitoring of SIMRS by relevant units, attention to factors influencing SIMRS adoption by users, and regular training related to the operation of the SIMRS application. Efforts to improve operational skills in the aspects of system quality, information quality, service quality, organizational structure, and organizational environment of SIMRS are crucial to optimize the net benefits generated by SIMRS.